The Effect of Minimal-Dose S-Ketamine Administration Post-Surgery on Opioids Consumption and Functional Rehabilitation Exercises in Patients Undergoing Minimally Invasive Radical Resection of Esophageal Cancer - Xie J; Shen F; Wang X; Yao J; Zhou L; Huang L; Sun J (Therapeutics and Clinical Risk Management)
Jue Xie,1 Fangming Shen,1 Xingming Wang,2 Juan Yao,1 Lingzhen Zhou,3 Luxin Huang,1 Jie Sun1 1Department of Anesthesiology, Surgery and Pain Management & Key Laboratory of Clinical Science and Research, Zhongda Hospital Southeast University, Southeast University School of Medicine, Nanjing, Jiangsu, People’s Republic of China; 2Department of Anesthesiology, Pain and Perioperative Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, 450052, People’s Republic of China; 3Department of Thoracic Surgery, Zhongda Hospital Southeast University, Southeast University School of Medicine, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Jie Sun, Email dgsunjie@hotmail.comStudy Objective: To examine the impact of minimal-dose S-ketamine on postoperative analgesia in patients undergoing minimally invasive radical resection for esophageal cancer, with a focus on reducing opioid consumption, enhancing analgesic quality, and facilitating postoperative recovery.Methods: A total of 216 patients undergoing minimally invasive radical resection of esophageal cancer under general anesthesia were randomly assigned into two groups (S-ketamine and control group), receiving intravenous S-ketamine (0.015 mg/kg/h) or an equal volume of saline for 48 h postoperatively. The primary outcome was cumulative oxycodone consumption in the first 48 h postoperatively. Secondary outcomes included functional activity score (FAS) after one bolus administration, numerical rating scale (NRS) pain scores at rest and when coughing, cumulative oxycodone consumption in different time periods, incidence of postoperative nausea and vomiting (PONV), level of sedation (LOS) score, time to first postoperative flatulence, postoperative delirium, activities of daily living assessed by BI (Barthel Index) and so on.Main Results: The postoperative opioid consumption within 48 hours in S-ketamine group was significantly lower than those in placebo group (P < 0.001), and the difference between the two groups was 40% (mean: 44.5 mg vs 74.8 mg). FAS after one bolus administration and BI in the S-ketamine group were notably superior to those in the control group (P < 0.001). There were Statistical differences between the two groups in the NRS scores at rest at postoperative hour 48 (P = 0.001) and the NRS scores when coughing at postoperative hour 12 (P = 0.011) with mean differences of − 0.3 and 0.4, respectively.Conclusion: Minimal-dose S-ketamine for managing acute postoperative pain in patients undergoing radical resection for esophageal cancer led to a 40% reduction in opioid consumption and promoted rehabilitation.Key words: S-ketamine, minimal dose, esophageal cancer, postoperative analgesia